2022
DOI: 10.1021/acscatal.2c02353
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Trends and Role of Adsorbate–Adsorbate Interactions in CO Hydrogenation on Rhodium Catalysts

Abstract: Predictive-quality computational modeling of heterogeneously catalyzed reactions has emerged as an important tool for the analysis and assessment of activity and activity trends. In contrast, more subtle selectivities and selectivity trends still pose a significant challenge to prevalent microkinetic modeling approaches that typically employ a mean-field approximation (MFA). Here, we focus on CO hydrogenation on Rh catalysts with the possible products methane, acetaldehyde, ethanol, and water. This reaction ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…In these elementary steps, various C–O bond dissociation ways (including CO*, CHO*, COH*, CH 2 O*, CHOH*, CH 3 O*, and CH 2 OH* dissociation) and C–C coupling (C*–CO*, CH*–CO*, CH 2 *–CO*, and CH 3 *–CO* coupling) have been taken into account. The other C–C coupling possibilities, such as CH x * –CHO* and CH x * –COH * coupling, are not considered either because CO* coverage has been proved to be the most dominant species on the Rh-based catalyst. ,, In the sight of the reaction rate, the CH x intermediates are more likely to couple with adsorbed CO*. It is worth noting that the acetaldehyde (CH 3 CHO) is chosen as the target C 2 -oxy product because it was supposed to be the main C 2 -oxy on Rh-based catalysts. , As for the byproducts, only the methane (CH 4 ) production is considered in the MK model, while CH 3 OH is not involved.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these elementary steps, various C–O bond dissociation ways (including CO*, CHO*, COH*, CH 2 O*, CHOH*, CH 3 O*, and CH 2 OH* dissociation) and C–C coupling (C*–CO*, CH*–CO*, CH 2 *–CO*, and CH 3 *–CO* coupling) have been taken into account. The other C–C coupling possibilities, such as CH x * –CHO* and CH x * –COH * coupling, are not considered either because CO* coverage has been proved to be the most dominant species on the Rh-based catalyst. ,, In the sight of the reaction rate, the CH x intermediates are more likely to couple with adsorbed CO*. It is worth noting that the acetaldehyde (CH 3 CHO) is chosen as the target C 2 -oxy product because it was supposed to be the main C 2 -oxy on Rh-based catalysts. , As for the byproducts, only the methane (CH 4 ) production is considered in the MK model, while CH 3 OH is not involved.…”
Section: Resultsmentioning
confidence: 99%
“…We started by studying the mechanism of syngas conversion on the pure Rh(111) surface and clarifying the challenges of C 2oxy production. According to both theoretical and experimental evidences, the Rh terrace facet (111) should be mainly responsible for the C 2 -oxy production, although it is less active 10,18,20 In the sight of the reaction rate, the CH x intermediates are more likely to couple with adsorbed CO*. It is worth noting that the acetaldehyde (CH 3 CHO) is chosen as the target C 2oxy product because it was supposed to be the main C 2 -oxy on Rh-based catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,5,6 Experimental and theoretical studies had shown that under-coordinated surfaces have low selectivity towards C 2+ oxygenates 6 and that less active terrace sites have some selectivity towards the desired products. 7 A more recent work has shown that the previous treatment of adsorbate-adsorbate interactions on Rh(111) surfaces was inadequate and arrived at the opposite conclusion for Rh, 8 so the understanding of this chemistry is still evolving. To form multi-carbon oxygenates, the catalyst must be simultaneously good at disassociating *CO to form *CH x intermediates on the surface and able to maintain *CO such that it may be inserted into the *CH x intermediates.…”
Section: Introductionmentioning
confidence: 99%